Investigation on Rattle of Gears under Random Loading - Wen, Yubing; Yang, Jianming (Journal of Applied Nonlinear Dynamics, 2026)
This paper investigates the random rattle motion of a single stage spur gear pair subjected to deterministic and random excitation. The motion is treated separately as free flight between the boundaries and the instant impact at the two boundaries. Numerical path integration method is applied to obtain the probability density of the response during free flight. Monte Carlo simulation is also conducted to verify the efficiency and accuracy of path integration in solving this strongly nonlinear dynamic problem. Comparison between results from path integration and Monte Carlo simulation is made and good agreement is achieved.